Can Digital Rectal Examination Identify the Subtype of Dyssynergic Disorders as Well as High Resolution Anorectal Manometry? - Philippe Onana Ndong; Karine Baumstarck; Véronique Vitton (JGH Open)
ABSTRACT Background and Aims Diagnosing dyssynergic disorders (DD) often requires 3D high‐definition anorectal manometry (3D‐HRAM), raising concerns about cost, availability, and delayed referral. Digital rectal examination (DRE) offers a reliable, cost‐effective alternative for DD diagnosis. This study aimed to assess DRE's capability to classify DD patients into the four subtypes outlined in Rao's classification. Methods This retrospective monocentric study involved patients diagnosed with DD through 3D‐HRAM. After initial 3D‐HRAM performed by one physician, patients underwent a clinical examination, including DRE by a second senior clinician blinded to DD subtypes. Statistical tests measured the correlation between DRE and HRAM in classifying the four DD subtypes. Results The study included 200 patients, revealing commendable overall agreement between DRE and 3D‐HRAM (Kappa = 0.658). For subtype diagnosis, correlation was substantial for Subtypes I, II, and IV (0.679, 0.741, 0.649, respectively) and moderate for Subtype III (Kappa = 0.325). Conclusion DRE demonstrates satisfactory performance in diagnosing the four subtypes of DD. Enhanced training in DRE, emphasizing functional information, has the potential to reduce reliance on additional tests, thereby mitigating economic and organizational impacts.